1994
DOI: 10.1096/fasebj.8.11.8070630
|View full text |Cite
|
Sign up to set email alerts
|

Calpain: new perspectives in molecular diversity and physiological‐pathological involvement

Abstract: Calpain, calcium-activated neutral protease, stands as a unique receptor for calcium signals in biological systems; its activation leads to irreversible proteolytic processing of substrate proteins, modifying cellular situations in a manner distinct from that of reversible processes including the phosphorylation-dephosphorylation reactions. Because the enzyme participates not only in normal intracellular signal transduction cascades but also in various pathological states including ischemia, calpain research h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
436
0
6

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 642 publications
(455 citation statements)
references
References 5 publications
13
436
0
6
Order By: Relevance
“…Investigation of the production of specific breakdown products (FBDP) of substrates specific to calpain proteolysis has proved useful in detecting calpain activity in nervous and sensory tissues (Siman et al, 1984;Saido et al, 1993Saido et al, , 1994Blomgren et al, 1995;Shields et al, 1999;Rajgopal and Vemuri, 2002;Ladrech et al, 2004 among others). Among these substrates, fodrin, the neuronal form of spectrin, is a specific actin cross-linking protein that is cleaved by calpain to a greater extent than other substrates.…”
Section: Hal Author Manuscript Inserm-00145385 Versionmentioning
confidence: 99%
“…Investigation of the production of specific breakdown products (FBDP) of substrates specific to calpain proteolysis has proved useful in detecting calpain activity in nervous and sensory tissues (Siman et al, 1984;Saido et al, 1993Saido et al, , 1994Blomgren et al, 1995;Shields et al, 1999;Rajgopal and Vemuri, 2002;Ladrech et al, 2004 among others). Among these substrates, fodrin, the neuronal form of spectrin, is a specific actin cross-linking protein that is cleaved by calpain to a greater extent than other substrates.…”
Section: Hal Author Manuscript Inserm-00145385 Versionmentioning
confidence: 99%
“…It has been shown that calcium overload leads to neurodegeneration in cerebral ischemia (Choi, 1995). Excessive calcium levels are responsible for activation of intracellular calcium proteases, such as calpains, which play a pivotal role in cytoskeletal degeneration and ischemic cell death (Saido et al, 1994;Wang and Yuen, 1994). Calpain is a cysteine protease which is overactivated in several pathological conditions, including all forms of excitotoxicity (Azuma et al, 1991;Siman and Noszek, 1988;Wang and Yuen, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The two major calpain isozymes, m-calpain (calpain I, m-CANP) and m-calpain (calpain II, m-CANP) require approximately 10 75 and 10 73 M Ca 2+ , respectively, for activity in vitro (Saido et al, 1994;Suzuki et al, 1992). There are other calpain gene family members which are distributed in speci®c tissues (Suzuki et al, 1992).…”
Section: Introductionmentioning
confidence: 99%